Effect of self-assembled nanofibrous silk/polycaprolactone layer on the osteoconductivity and mechanical properties of biphasic calcium phosphate scaffolds - Roohani-Esfahani, Seyed-Iman; Ellis-Behnke, Rutledge (Acta biomaterialia, 2012)
Abstract: We here present the first successful report on combining nanostructured silk and poly(ε-caprolactone) (PCL) with a ceramic scaffold to produce a composite scaffold that is highly porous (porosity ∼85%, pore size ∼500 μm, ∼100% interconnectivity), strong and non-brittle with a surface that resembles extracellular matrix (ECM).